Economic feasibility of short rotation coppice willows for biomass production in Kashmir - Masoodi, T.H.; Bhat, G.M.; Sofi, P.A.; Gangoo, S.A.; Malik, A.R.; Sheikh, M.Q.; Mir, A.A. (Indian Journal of Agroforestry, 2020)
The production potential and economic feasibility of willows for biomass production was performed for short rotation coppice (SRC) crop managed under locally developed planting design that accommodated around 17094 plants ha-1. The first rotation of this crop harvested after 4 years of plantation yielded 15.55 tons (fresh weight basis) of biomass ha-1 yr-1 which increased to 23.41 tons ha-1 yr-1 after 2nd rotation cycle of 3 years. The high biomass production potential under this dynamic agro-botany-forestry system achieved as a result of rapid growth of plants induced by close spacing proved to be most remunerative with an expected revenue of Rs 0.87 to 1.75 lakhs ha-1 ( tentative rate of Rs. 7.50 /kg of fuel wood) from the land generally unsuitable for agricultural crops. The analysis of data reveals that the gross and net income realized from this plantation after two rotation cycles amounts to Rs 8,76,750 and 4,96,255 ha-1 with net present worth of Rs 2,00,663 and B: C ratio of Rs 1.73 for every rupee invested at a discount rate of 12%. The system is thus so viable that it provides quick and high returns along with many opportunities for permanent employment. Despite this huge economic potential, any attempt to promote the technology of SRC forestry in Kashmir cannot succeed unless parallel efforts are made to develop biomass based energy sector which will in turn be strongly influenced if plantation subsidy is given as start-up expenditure to the farmers.